2016
DOI: 10.1523/jneurosci.2327-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

New Insight in Cold Pain: Role of Ion Channels, Modulation, and Clinical Perspectives

Abstract: Cold temperature detection involves the process of sensory transduction in cutaneous primary sensory nerve terminals, which converts thermal stimuli into depolarizations of the membrane. This transformation into electrical signals is followed by the subsequent propagation of action potentials in cold-sensitive afferent nerve fibers. A large array of ion channels shapes this process; however, the precise contribution of specific ion channel subtypes to cold perception and cold pain remains elusive. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 55 publications
1
37
1
Order By: Relevance
“…TRPA1 was initially proposed to be involved in noxious cold sensing (Story et al 2003) but recent reports have questioned its role, hypothesizing that it might be regulating cold sensitivity indirectly, rather than acting as a cold-sensing receptor (Lolignier et al 2016;Yarmolinsky et al 2016;Winter et al 2017). If TRESK and TRPA1 are partially co-expressed in some neurons, one would expect an increase in the responses triggered by TRPA1 activation but, to our surprise, we observed the opposite effect despite TRPA1 mRNA expression being unchanged.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…TRPA1 was initially proposed to be involved in noxious cold sensing (Story et al 2003) but recent reports have questioned its role, hypothesizing that it might be regulating cold sensitivity indirectly, rather than acting as a cold-sensing receptor (Lolignier et al 2016;Yarmolinsky et al 2016;Winter et al 2017). If TRESK and TRPA1 are partially co-expressed in some neurons, one would expect an increase in the responses triggered by TRPA1 activation but, to our surprise, we observed the opposite effect despite TRPA1 mRNA expression being unchanged.…”
Section: Discussioncontrasting
confidence: 57%
“…) but recent reports have questioned its role, hypothesizing that it might be regulating cold sensitivity indirectly, rather than acting as a cold‐sensing receptor (Lolignier et al . ; Yarmolinsky et al . ; Winter et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the notion that other nociceptors, such as polymodal nociceptors, may also be responsive to noxious doses of menthol. A recent review suggested that a variety of other TRP, potassium and sodium channels may be involved in the transduction or modulation of cold pain from peripheral afferents (Lolignier et al, 2016). However, it is unclear if any of these channels could be directly activated by menthol in the absence of TRPM8.…”
Section: Discussionmentioning
confidence: 99%
“…These contradictory effects of cold in warm-blooded animals may be due to differences at the molecular, cellular, or circuit level (Vriens et al, 2014; Palkar et al, 2015; Lolignier et al, 2016). At the molecular level, temperature-sensitive transient receptor potential (thermoTRP) channels such as TRPM8 and TRPA1 have been reported to detect cold temperatures (Talavera et al, 2008).…”
Section: Introductionmentioning
confidence: 99%